2019
DOI: 10.6007/ijarbss/v9-i1/5894
|View full text |Cite
|
Sign up to set email alerts
|

The Teaching of Malay Essay Writing based on an Authentic Approach

Abstract: In this paper, the authors discuss the principles and models of authentic learning, which have been proposed by several leading experts in the field of authentic learning. Among the principles, authentic learning materials, authentic assessment, and teaching and learning activities based on the real world are the core principles shared by most models. In particular, the authors propose an authentic learning model that will be used for the essay teaching process in the classroom consisting of six important prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…A more authentic assessment of writing ability would involve students in writing a whole, meaningful text (Osman, et al, 2019). Students might write the kind of text that they would write in their real life, either now or in the future.…”
Section: Authenticity In Assessment Tasks and Materialsmentioning
confidence: 99%
“…A more authentic assessment of writing ability would involve students in writing a whole, meaningful text (Osman, et al, 2019). Students might write the kind of text that they would write in their real life, either now or in the future.…”
Section: Authenticity In Assessment Tasks and Materialsmentioning
confidence: 99%
“…This is because VAK learning styles are more famous and easy to use in identifying one's learning style (Febriani, 2018;Zulkipli et al, 2019). Thus, appropriate learning styles in the subject of Mathematics help students to understand mathematical concepts more effectively (Cimermanová, 2018), in addition to creating a more fun mathematics learning atmosphere since it is more interactive (Osman et al, 2019). Study by Asio (2020) found that respondents tend to procrastinate with their academics.…”
Section: Introductionmentioning
confidence: 99%